Necesidad de tipificar como delito en el libro ii, título ii, capítulo viii del código penal ecuatoriano la declaración falsa de las utilidades por parte del empleador - Roman Villa, Elizabeth Margarita (2014)
In Art. 33 of the Constitution of the Republic of Ecuador, states that work is a right and a social duty and an economic, source of personal fulfillment and economic base. The State shall guarantee working people full respect for their dignity and decent living wages and fair remuneration and performance of a healthy and freely chosen or accepted. Paragraph 2 of Article 66 of the Constitution of the Republic of Ecuador guarantees the right to a decent life, ensuring health, food and nutrition, clean water, shelter, sanitation, education, labor, employment, rest and leisure, culture physical, dress, social security and other social facilities. In accordance with this statutory provision in Article 325, ibid, mentioned that the state guarantees the right to work. All forms of work are recognized as an employee or self-employed, including self-support work and human care; and as productive social actors, to all workers and employees. The Art. 97 of the Labour Code, expresses the employer or enterprise recognizes the benefit of their employees to fifteen percent of the net profits. This percentage is distributed as follows: Ten percent of divided for company employees, without regard to the remuneration received by each during the year for the cast and will be delivered directly to the worker. The remaining five percent will be delivered directly to employees of the company, in proportion to their dependents, meaning these the spouse or common-law (...). The Art. 107 of the Labour Code establishes "Penalties for false declaration of utilidades.- In Minister for Industrial Relations, punishable by a fine of ten to twenty minimum wages, according to the economic capacity, the company, in which it is found previous audit of the Internal Revenue Service, falsehood attributable to fraud, on data regarding utilities, or use of irregular procedures to avoid delivery percentage or to reduce the amount thereof. I note that totally derisory fines are set out in the said statute, (ten US dollars or eighty US dollars), against the employer on the basis of a series of ruses, tries to violate a legally established as the payment of employee profit . In my opinion I think it right to employee participation in corporate profits is also an important tool to contribute to the redistribution of wealth and social justice, a mechanism that boosts productivity, since participation is conceived as a productive effort remuneration of employees. Hence the importance of promoting its full implementation, thus the Ecuadorian State must protect this right. In this sense I think that if proven fraud, we must establish this figure as a crime, to somehow stop the train of abuses that some employers committed against the worker, as there are companies that reported zero profit or totally unrealistic amounts to evade payment, harming not only the worker, but the Ecuadorian State. In Comprehensive Organic Penal Code, any criminal sanction for the employer using a series of guidelines for reporting unrealistic profits is not set. But when demanding their rights worker, the employer simply terminates the employment relationship, breach of the right to work is constitutionally guaranteed. Under these constitutional provisions is necessary to define under Ecuadorian penal law, misrepresentation of earnings from the employer, because according to Article 25 of the Ecuadorian Criminal Code, "The offenses set out the relevant criminal conduct", ie the criminal offense must be established in order to be sanctioned by the Criminal Code of Integral.